Analysis of the Application of Business Ethics in Online Buying and Selling Transactions on the Shopee Marketplace - irma rahmayani marpaung; Zuhrinal M Nawawi; Nuri Aslami (International Journal Labs, 2022)
Background: In online buying and selling transactions, a seller is required to not intentionally contradict his words and actions in his business. The seller must have a mandate by displaying an attitude of openness, honesty, optimal service, and doing good with all things, especially in relation to public service. Objective: aims to analyze the application of business ethics in online buying and selling transactions on the shopee marketplace. This type of research is juridical-normative or normative legal research. Methods: This type of research is juridical-normative or normative legal research. Results: The results show that: the application of business ethics in online buying and selling transactions on the shopee marketplace, has not implemented good business ethics. Because there are still acts of lying and also posting pictures that do not match the original. Conslusion: From the discussion in this study, it can be concluded that the application of business ethics in online buying and selling transactions in the shopee marketplace still has not implemented business ethics properly. Because the seller still discriminates against the buyer.